2016
DOI: 10.1108/jap-11-2015-0033
|View full text |Cite
|
Sign up to set email alerts
|

Women aged 45-64 and IPV in Cyprus

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…34 This cultural acceptability provides Middle Eastern women with the ability to keep their victimization silent, and therefore not seek help. 35 However, research suggests that greater awareness of what DV entails, having more resources available to report DV, as well as improved financial independence for women may help change the perception of DV. For example, researchers in the Republic of Cyprus found that middle-aged women reported the highest percentage of DV due to more knowledge about the types of DV, as well as having greater social support.…”
Section: Selection Processmentioning
confidence: 99%
“…34 This cultural acceptability provides Middle Eastern women with the ability to keep their victimization silent, and therefore not seek help. 35 However, research suggests that greater awareness of what DV entails, having more resources available to report DV, as well as improved financial independence for women may help change the perception of DV. For example, researchers in the Republic of Cyprus found that middle-aged women reported the highest percentage of DV due to more knowledge about the types of DV, as well as having greater social support.…”
Section: Selection Processmentioning
confidence: 99%